Multilingualism and Multiculturalism : Language Teaching and Learning - Karpava, Sviatlana (Language and Linguistics E-Books Online, Collection 2024., 2025)
This edited volume emphasizes the critical role of macro, meso and micro factors in development of multilingual and multicultural environment for learning and teaching. The collection advocates for inclusive education, safe spaces for both teachers and students, teachers and students' agency, educators' reflection, and continuous professional development. It promotes the idea of multilingualism as a learning resource by overcoming a monolingual bias and language ideologies and by taking learners' individual differences, social, economic and political factors into consideration. The originality of this collection is in its diversity spanning linguistic, sociocultural, and pedagogical dimensions. See Less